2020
DOI: 10.1021/acsabm.9b00720
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Biosynthesized Superparamagnetic Iron Oxide Nanoparticles (SPIONS) Induce Efficient Hyperthermia in Cancer Cells

Abstract: Despite the promising role of magnetic hyperthermia in cancer therapy, its use in patients has been restricted by hurdles that include inefficient targeting of magnetic particles to the tumor site, limited bioavailability, and high toxicity, etc. Taking advantage of the unique metabolic property of cancer cells, we explored the potential of these cells to biosynthesize magnetic nanoparticles for potential hyperthermia applications. Treatment of cancer cells with a mixture of FeCl 2 and zinc gluconate resulted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 54 publications
(89 reference statements)
1
21
0
Order By: Relevance
“…It is likely that ROS is involved in the biomineralization process, as only those microbes expressing high levels of ROS revealed intracellular iron accumulation and nanoparticle synthesis (Table S1). In an earlier study, we had reported ROS involvement in inducing MNP synthesis in eukaryotic cells treated with a similar combination of Fe and Zn precursors [21].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is likely that ROS is involved in the biomineralization process, as only those microbes expressing high levels of ROS revealed intracellular iron accumulation and nanoparticle synthesis (Table S1). In an earlier study, we had reported ROS involvement in inducing MNP synthesis in eukaryotic cells treated with a similar combination of Fe and Zn precursors [21].…”
Section: Resultsmentioning
confidence: 99%
“…Whereas several studies have compared the influence of either Fe / Zn on microbes, no study has yet shown their combined effect. Recently we had observed MNP formation in eukaryotic cells exposed to ferrous chloride and zinc gluconate [21]. Given the importance of iron and zinc to bacteria, the study was extended to bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…Kaushik et al. [ 216 ] reported a biosynthesis mechanism to synthesize nanoparticles inside tumor cells to induce magnetic hyperthermia. Briefly, the investigators exposed the cancer cells to FeCl 2 and zinc gluconate.…”
Section: Biomedical Applications Of Mnpsmentioning
confidence: 99%
“…The cellular environment experienced 4°C–5°C elevation in temperature as a result of 30 minutes exposure to an alternating magnetic field. [ 216 ] As cancer cells have a higher ROS level than normal healthy cells, particle synthesis was not carried out in regular healthy cells due to lower H 2 O 2 levels. Hence the mechanism is inherently targeting only cancerous cells and once the biosynthesis of the particles is done, the particles can be utilized to induce cell death using magnetic hyperthermia.…”
Section: Biomedical Applications Of Mnpsmentioning
confidence: 99%
“…To overcome the above stated limitations, Furostanol Saponin (FS) present in the Fenugreek seeds extract is utilized to synthesize iron oxides of size and shape-controlled nanostructures along with control over their growth direction. For the first time, this proposed methodology has been used to produce high yield and high quality of γ-Fe 2 O 3 nanograsses (NGs), nanowires (NWs) and nanospheres (NSs) via biogenic (greener) route 23,24 . The resultant γ-Fe 2 O 3 nanostructures are characterized by using various spectroscopic and microscopic techniques.…”
Section: Scientific Reportsmentioning
confidence: 99%